Significance of blood pressure variability in normotensive individuals as a risk factor of developing hypertension - Hiroyuki Takase; Tomonori Sugiura; Sumiyo Yamashita; Naomi Kawakatsu; Kazusa Hayashi; Fumihiko Kin; Takeru Isogaki; Yasuaki Dohi (Blood Pressure)
Purpose Visit-to-visit blood pressure variability is a strong predictor of the incidence of cardiovascular events and target organ damage due to hypertension. The present study investigated whether year-to-year blood pressure variability predicts the risk of hypertension in the Japanese general population.Materials and methods This study analysed 2806 normotensive individuals who participated in our physical check-up program for five years in a row from 2008 to 2013. The average, standard deviation, coefficient of variation, average real variability, and highest value of systolic blood pressure in the five consecutive visits were determined and used as baseline data. The participants were followed up for the next 6 years with the development of ‘high blood pressure’, an average blood pressure level of ≥140/90 mmHg or the use of antihypertensive medications, as the endpoint.Result During follow-up, ‘high blood pressure’ developed in 389 participants (13.9%, 29.5 per 1 000 person-years). The incidence increased across the quartiles of standard deviation and average real variability, while the average and highest systolic blood pressure had the most prominent impact on the development of ‘high blood pressure’. Multivariate logistic regression analysis adjusted for possible risk factors indicated that the average, standard deviation, average real variability, and highest blood pressure, but not the coefficient of variation of systolic blood pressure, were significant predictors of ‘high blood pressure’.Conclusion Increased year-to-year blood pressure variability predicts the risk of hypertension in the general normotensive population. The highest blood pressure in the preceding years may also be a strong predictor of the risk of hypertension.